Old English Poetry and Its Legacy - Bjork, Robert E. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection focuses on the legacy of Old English poetry and includes new interpretations of works such as Exeter Book Riddle 5, which provides an enduring legacy of social critique crafted through humor; the three manuscripts that contain the Solomon and Saturn dialogues, which reveal a shift in the use of poetry over time; Fates of the Apostles in which a previously unseen eighth rune is semiotically operative along with Cynewulf's signature; The Wife's Lament, in which the cave occupied by the wife has its archeological antecedents in early medieval rock-cut buildings; The Ruin, in which both the poem's text and the silent spaces of wyrd's traces are inscribed upon the material manuscript; the history of the reception of the riddles, which is instrumental in inspiring one of the acknowledged classic ghost stories of the twentieth century; tears and weeping in the whole corpus of Old English literature; and Beowulf, in which the figures of the stag and wolf play an important role in the thematic design of the poem but have not been examined before. The reprint is prefaced with a detailed account of the scholarly contributions to Old English studies by John D. Niles.